Management of patients with chronic fatigue syndrome and the role of physical rehabilitation - Bogdanovska, Nadezhda; Kalonova, Iryna; Pozmogova, Natalia (Journal of Education, Health and Sport, 2017)
Chronic Fatigue Syndrome (CFS) leads to a decrease in ability to work, patients may not perform the usual operation, joins apathy, often develop depression, anxiety, hypochondria, disrupted social adaptation. Purpose: to consider the features of management of patients with chronic fatigue syndrome and the role of physical rehabilitation in it. Methods of research: analysis of scientific literature, synthesis and generalization. Results. CFS has a number of features that need to be considered in the management of patients, and in the construction of physical rehabilitation programs. The problem of рost-exertional malaise is solved with the help of management of activity and distribution of rest throughout the day. Also in the management of patients with chronic fatigue syndrome, it is important to pay attention to the formation of sleep hygiene and the use of physical rehabilitation to eliminate pain in the muscles and joints. Conclusions: Rehabilitation specialists or physical therapists should help patients adapt to life with CFS, teach patients to listen to their body, perform systematic exercises to avoid deconditioning.